Virtually Amish Preserving Community at the Internet's Margins - Ems, Lindsay (Acting with Technology, 2022)
How the Amish have adopted certain digital tools in ways that allow them to work and live according to their own value system. The Amish are famous for their disconnection from the modern world and all its devices. But, as Lindsay Ems shows in Virtually Amish, Old Order Amish today are selectively engaging with digital technology. The Amish need digital tools to participate in the economy-websites for ecommerce, for example, and cell phones for communication on the road-but they have developed strategies for making limited use of these tools while still living and working according to the values of their community. The way they do this, Ems suggests, holds lessons for all of us about resisting the negative forces of what has been called "high-tech capitalism." Ems shows how the Amish do not allow technology to drive their behavior; instead, they actively configure their sociotechnical world to align with their values and protect their community's autonomy. Drawing on extensive ethnographic fieldwork conducted in two Old Order Amish settlements in Indiana, Ems explores explicit rules and implicit norms as innovations for resisting negative impacts of digital technology. She describes the ingenious contraptions the Amish devise-including "the black-box phone," a landline phone attached to a device that connects to a cellular network when plugged into a car's cigarette lighter-and considers the value of human-centered approaches to communication. Non-Amish technology users would do well to take note of Amish methods of adopting digital technologies in ways that empower people and acknowledge their shared humanity.